EMTP IMPLEMENTATION OF A MONTE CARLO METHOD FOR LIGHTNING PERFORMANCE ANALYSIS OF TRANSMISSION LINES - Martínez-Velasco,Juan A (Universidad de Tarapacá., 2008)
An accurate calculation of lightning overvoltages is an important issue for the analysis and design of overhead transmission lines. The different parts of a transmission line that are involved in lightning calculations must be represented taking into account the frequency ranges of transients associated to lightning. In addition, the procedures to be used in these calculations must be developed considering the random nature of lightning phenomena. Several simulation tools have been used to estimate the lightning performance of transmission lines. The most popular approaches are those based on a time-domain simulation technique for which adequate procedures and transmission line models have to be developed. This paper presents a summary of the computational efforts made by the authors for the development and implementation in an EMTP-like tool of a Monte Carlo procedure, as well as the models of some transmission line components, aimed at analyzing the lightning performance of transmission lines. An actual test line is used to illustrate the scope of this procedure and the type of studies that can be performed.